Model Distribusi Perjalanan Penumpang Domestik di Bandara Internasional Adi Soemarmo - Pratiwi, Dian Arga, Nurul Hidayati, Ph.D (2016)
Annual population growth rate will increase transport demand to meet daily needs. This condition is experienced by the air transport as well, including in Adi Sumarmo International Airport Surakarta. This study aims to determine the characteristics and the distribution pattern of domestic passengers in Adi Soemarmo. The required data consists of passenger growth rate, origin-destination trips, travel costs, travel time and mileage traveled. Analysis method is using Double Constraint Gravity Model (DCGM) with a negative exponential function, which would be predicted for the year 2020. The analysis shows the relative age of the domestic users are 26-35 years old, which is dominated by men (53%) and work as self-employed (37%). DCGM analysis results obtained an average annual passenger growth rate increased by 35,64 %. Travel distribution domestic passengers in 2020 obtained: SOC - BDO 153.318 trips , SOC - BPN 414.177 trips , SOC - BTM 159.069 trips, SOC - CGK 5.348.790 trips , SOC - DPS 372.033 trips , SOC - HLP 344.787 trips , dan SOC - SUB 588.166 trips.